The horse and his boy - Lewis, C. S. (Clive Staples), 1898-1963.; Baynes, Pauline (New York : HarperCollins, 1994)
Bree, a talking horse, and Shasta, a young boy, are joined by the four English children and Aslan to help save Narnia from invasion.
5.3
5-8
Keywords: Horses -- Juvenile fiction; Narnia (Imaginary place) -- Juvenile fiction; Fantasy; Horses -- Fiction; Narnia (Imaginary place) -- Fiction; Horses -- Fiction; Narnia (Imaginary place) -- Fiction; Fantastic fiction